2017
DOI: 10.1159/000480083
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic Patterns of Indium-111 Oxine-Labeled White Blood Cell Imaging of Gram-Negative versus Gram-Positive Vertebral Osteomyelitis

Abstract: Objective: The goal of the study was to investigate whether or not gram-negative organisms that secrete antichemotactic factors cause the nonaccumulation pattern of 111In-oxine-labeled white blood cell (111In-WBC) scans. Materials and Methods:Staphylococcus aureus (gram-positive) (group 1) was injected into 25 rabbits and Escherichia coli (gram-negative) (group 2) into another 25 to induce infection in the lumbar vertebrae or left thigh bone (femur). Sixteen successfully infected and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…[ 22 ] Moreover, decreased leukocyte uptake is frequently encountered in spinal infection, especially for gram-negative vertebral infection, with the accuracy being 66% for detecting vertebral osteomyelitis. [ 27 , 28 ] Ga-67 scintigraphy has high diagnostic ability for vertebral osteomyelitis, and is known as the primary gamma camera imaging method for vertebral osteomyelitis. [ 20 , 22 ] Nevertheless, it is not an optimal radionuclide for gamma camera imaging and the relatively long interval between radiotracer injection and imaging precludes the wide use of Ga-67 scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Moreover, decreased leukocyte uptake is frequently encountered in spinal infection, especially for gram-negative vertebral infection, with the accuracy being 66% for detecting vertebral osteomyelitis. [ 27 , 28 ] Ga-67 scintigraphy has high diagnostic ability for vertebral osteomyelitis, and is known as the primary gamma camera imaging method for vertebral osteomyelitis. [ 20 , 22 ] Nevertheless, it is not an optimal radionuclide for gamma camera imaging and the relatively long interval between radiotracer injection and imaging precludes the wide use of Ga-67 scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical study, Elgazzar et al . [12] induced osteomyelitis in the vertebral and femoral bones in rabbits. The expected increased labeled WBCs uptake was observed in 14 out of the 16 sites, including both femoral and vertebral, of Gram-positive induced osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Elgazzar et al . [12] suggested that the false-negative results in cases of Gram-negative osteomyelitis could be due to the secretion of anti-chemotactic factors by these organisms with defective chemotaxis. Gram-negative organisms, unlike Gram-positive ones, are known to be associated with defective chemotaxis as they secrete anti-chemotactic factors as reported by some studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations